Ethnobotanical database development and screening of medicinal plants in villages under the Jongilanga Traditional Council, Mpumalanga - Tshikalange, T.E. (Thilivhali Emmanuel) (University of Pretoria, 2021)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2015.